FORMULASI MODERASI BERAGAMA DALAM PEMIKIRAN YUSUF AL-QARDHAWI SEBAGAI BASIS MEWUJUDKAN MASYARAKAT MADANI - Dzikrul Hakim Tafuzi Mu'iz; Uril Bahruddin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
This study aims to explain the formulation of religious moderation in Yusuf al-Qardhawi's thoughts and the relevant values of religious moderation in civil society. The data was obtained using the documentation method of Yusuf al-Qardhawi's thoughts on religious moderation which can be used as a reference for the formation of civil society. The findings of this study emphasize two aspects: first, the concept of forming a civil society stems from Yusuf al-Qardhawi's thought of religious moderation and the values that must exist in civil society; second, indicators that can be used as benchmarks to assess the achievements of civil society which include: egalitarian (equality), respect for achievement, openness, tolerance, and deliberation. Therefore, an in-depth study is needed to measure the civilization that has been built today as an effort to achieve welfare targets in the form of civil society.